The Role of Law in the Implementation of Islamic Social Reporting: A Case Study of Islamic Banking in Asia - Warno Warno; Tarmizi Achmad; Puji Harto; Bill Pangayow (Al-Ahkam, 2025)
This study aims to analyze the influence of government regulation on the implementation of Islamic Social Reporting (ISR) in Islamic banking across five countries: Indonesia, Malaysia, Kuwait, the United Arab Emirates, and Bahrain. ISR is a form of sustainability reporting based on Sharia principles, covering six main dimensions: responsibility to fund providers, employees, society, the environment, products, and compliance with regulations. This study employs a qualitative approach using content analysis of annual and sustainability reports of Islamic banks from 2014 to 2023. The findings show that regulations such as POJK No. 51/2017 in Indonesia, the Islamic Financial Services Act (IFSA) 2013 and ESG Guidelines in Malaysia, sustainability policies from the Central Bank of Kuwait, the Securities and Commodities Authority (SCA) guidelines in the United Arab Emirates, and reporting standards from the Central Bank of Bahrain have contributed to improvements in ISR practices, both in terms of formal compliance and the substance of the content. However, most reporting remains administrative in nature and does not fully reflect the values of maqāṣid al-sharī’a. Therefore, this study recommends strengthening regulations that not only mandate reporting but also emphasize quality, depth, and the integration of Islamic values into sustainability practices in Islamic banking to achieve meaningful social and environmental.